Derivation of elastic fracture toughness for ductile metal pipes with circumferential external cracks under combined tension and bending. (1st June 2017) - Li, Chun-Qing; Fu, Guoyang; Yang, Wei; Yang, Shangtong
Highlights: An elastic fracture toughness model for pipes with circumferential cracks is derived. The significance is to use linear elastic fracture mechanics for ductile materials. Elastic fracture toughness increases with the increase of internal pressure. An increase in fracture toughness will result in a more ductile pipe failure. An increase in yield strength will result in a more brittle pipe failure. Abstract: Linear elastic fracture mechanics has been widely employed for fracture analysis of cracked pipes. For ductile metal pipes, the existence of plasticity eases the stress concentration at the crack front, which increases the fracture toughness of the pipe. Therefore, when using linear elastic fracture mechanics to predict the fracture failure of ductile pipes, the plastic portion of the fracture toughness should be excluded. This paper intends to derive an analytical model of elastic fracture toughness for ductile metal pipes with circumferential external surface cracks under combined axial tension and bending. The derived elastic fracture toughness is a function of crack geometry, material properties and loading conditions of the cracked pipe. The significance of the derived model is that the well established linear elastic fracture mechanics can be used for ductile materials in predicting the fracture failure. It is found in the paper that, the elastic fracture toughness increases with the increase of the internal pressure of the pipe and that an increase in fracture toughness and yield strength of the pipe materials will result in a more ductile and brittle pipe failure respectively. The derived analytical model enables more accurate prediction of fracture failure of ductile metal pipes with circumferential external cracks.